CORRELATIONS OF TELEROENTGENOGRAPHIC PARAMETERS OF THE JAWS WITH BASAL CRANIAL PARAMETERS IN UKRAINIAN JUVENILE MEN AND JUVENILE WOMEN WITH DIFFERENT FACIAL PROFILES ACCORDING TO SCHWARZ - Prokopenko, O.S.; Beliaiev, E.V.; Kravets, R.A.; Marynych, L.I.; Prokopenko, S.V. (World of Medicine and Biology, 2022)
Peculiarities of correlations between TRG-indices of the upper and lower jaws, intermaxillary indices that can be corrected during surgical and orthopedic treatment, and TRG-indices of the skull, which usually do not change during such interventions in Ukrainian juvenile men and juvenile women with orthognathic bite with different facial profiles according to Schwarz, were established. In juvenile men with the first face profile (back profile), the revealed reliable connections were mostly direct of medium strength and strong, and in juvenile women, almost the same number of direct and reverse connections of mostly medium strength were established. In juvenile men with the second face profile (straight profile), reliable connections were exclusively strong direct and strong inverse, while in juvenile women direct connections of medium strength prevailed. Both juvenile men and juvenile women with the third face profile (front profile) have mainly direct reliable relationships of medium strength.